Electoral Competition when Candidates are Better Informed than Voters - Thomas Jensen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2009)
In this paper we study the functioning of representative democracy when politicians are better informed than the electorate about conditions relevant for policy choice. We consider a model with two states of the world. The distribution of voters' preferred policies shifts with the state. The two candidates are both completely office-motivated but differ in state-dependent quality. Voters have some information about the state but candidates are better informed. If voters' information is unknown to the candidates when they take positions and sufficiently accurate then candidates will, in refined equilibrium, reveal their information by converging to the most likely median. If voters' information is not sufficiently accurate then there is polarization and the candidates'information is not revealed to the voters. We also show that if voters'information is known to the candidates then they will never reveal their information to the voters. The candidates will either pander by converging on the median that is most likely given only the voters'information or be polarized. With respect to welfare, if voters are well informed then they all prefer that their information is unknown to the candidates. However, if voters are not well informed then it is the other way around, all voters prefer that their information is known by the candidates.
Keywords: D72; D82; 330; electoral competition; uncertainty; information; candidate quality; Wahlverhalten; Asymmetrische Information; Entscheidung bei Unsicherheit; Politiker; Qualifikation; Neue politische Ökonomie